Lysophosphatidylinositol signalling and metabolic diseases - Ahmad Arifin, Syamsul; Falasca, Marco (2016)
Metabolism is a chemical process used by cells to transform food-derived nutrients, such as proteins, carbohydrates and fats, into chemical and thermal energy. Whenever an alteration of this process occurs, the chemical balance within the cells is impaired and this can affect their growth and response to the environment, leading to the development of a metabolic disease. Metabolic syndrome, a cluster of several metabolic risk factors such as abdominal obesity, insulin resistance, high cholesterol and high blood pressure, and atherogenic dyslipidaemia, is increasingly common in modern society. Metabolic syndrome, as well as other diseases, such as diabetes, obesity, hyperlipidaemia and hypertension, are associated with abnormal lipid metabolism. Cellular lipids are the major component of cell membranes; they represent also a valuable source of energy and therefore play a crucial role for both cellular and physiological energy homeostasis. In this review, we will focus on the physiological and pathophysiological roles of the lysophospholipid mediator lysophosphatidylinositol (LPI) and its receptor G-protein coupled receptor 55 (GPR55) in metabolic diseases. LPI is a bioactive lipid generated by phospholipase A (PLA) family of lipases which is believed to play an important role in several diseases. Indeed LPI can affect various functions such as cell growth, differentiation and motility in a number of cell-types. Recently published data suggest that LPI plays an important role in different physiological and pathological contexts, including a role in metabolism and glucose homeostasis.